THE INFLUENCE OF COMPETENCE, EDUCATION, AND WORKLOAD ON EMPLOYEE PERFORMANCE WITH WORK MOTIVATION AS AN INTERVENING VARIABLE IN THE SECRETARIAT OF THE BATAM CITY GOVERNMENT - Febro Febrian Pratama; Ramli; I Wayan Catra Yasa (CV. RADJA PUBLIKA, 2025)
This study aims to determine the direct and indirect relationships between competency, work experience, and information technology mastery on employee performance through work motivation as an intervening variable at the Regional Secretariat of Batam City. The population can provide useful information or data for a study. The population in this study consisted of 144 civil servants working at the Regional Secretariat of the Batam City Government. In this study, the sampling technique used is nonprobability sampling, specifically saturated sampling (census). The sample used in this study is the entire population of 144 civil servants at the Regional Secretariat of the Batam City Government. Data were collected via questionnaires and analyzed using validity and reliability tests, classical assumption tests, multiple regression analysis, and path analysis. The results is the direct effect of the Competence variable on the Employee Performance variable can be stated that there is a positive and significant effect between Competence and Employee Performance. The direct effect of the Education variable on the Employee Performance variable can be stated that there is a positive and significant effect between Education and Employee Performance. The direct effect of the Workload variable on the Employee Performance variable can be stated that there is a positive and significant relationship between Workload and Employee Performance. The direct effect of the Work Motivation variable on the Employee Performance variable can be stated that there is a positive and insignificant relationship between Work Motivation and Employee Performance. The direct influence of the Competence variable on the Work Motivation variable can be stated that there is a positive and significant influence between Competence and Work Motivation. The direct influence of the Education variable on the Work Motivation variable can be stated that there is a positive and significant influence between Education and Work Motivation. The direct effect of the Workload variable on the Work Motivation variable can be stated that there is a positive and significant relationship between Workload and Work Motivation. The indirect effect of the Competence variable on the Employee Performance variable with Work Motivation as the intervening variable can be stated that there is a positive and significant relationship between Competence and Employee Performance with Work Motivation as the intervening variable. The indirect effect of the Education variable on the Employee Performance variable with Work Motivation as the intervening variable can be stated that there is a positive and significant relationship between Education and Employee Performance with Work Motivation as the intervening variable. The indirect effect of the Workload variable on the Employee Performance variable with Work Motivation as an intervening variable can be stated that there is a positive and significant effect between Workload on Employee Performance with Work Motivation as an intervening variable.